2012
DOI: 10.1007/s12072-012-9409-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines are associated with postembolization fever and survival in hepatocellular carcinoma patients receiving transcatheter arterial chemoembolization

Abstract: TACE is associated with the modulation of serum angiogenic, inflammatory, and cell growth cytokines in HCC patients. Serum IL-6 correlates with post-TACE fever, and baseline serum VEGF independently predicts patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…Most of the treatment-non-naïve patients underwent TACE, and previous studies have demonstrated that serum IL-6 level increases after TACE and is correlated with post-TACE inflammation[13,14]. In these studies, the increase of serum IL-6 level occurred within several days after TACE and was attributed to a protective function of IL-6 against acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the treatment-non-naïve patients underwent TACE, and previous studies have demonstrated that serum IL-6 level increases after TACE and is correlated with post-TACE inflammation[13,14]. In these studies, the increase of serum IL-6 level occurred within several days after TACE and was attributed to a protective function of IL-6 against acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons could have contributed to the heterogeneity, including the constituent ratio of patients’ age, detection method, and a diverse source of samples in each study. For example, samples in two articles were from urine [16, 20], three from plasma/serum [10, 13, 17], and seven from tumor tissue [11, 12, 14, 15, 18, 19, 21]. Secondly, there were variable definitions of the cut-off value among these publications.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether TGF-β1 expression has the potential to predict HCC prognosis is inconsistent. For example, some articles reported that HCC patients with high TGF-β1 expression showed shorter OS and DFS/PFS [1012], while some other studies revealed negative findings on OS [13, 14]. There is a need to implement meta-analysis and larger sample evaluation, aiming to systematically elaborate on the prognostic power of TGF-β1 expression in HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…A key question is whether the ischemic damage imposed by TACE may facilitate priming to a broad range of previously inaccessible neoepitopes and exert synergistic antitumor effects with immunotherapy. TACE plays a role in activating a hypoxic response, promoting the release of vascular endothelial growth factor (VEGF) and other proangiogenic cytokines . Evidence suggests that PD‐L1 expression is transcriptionally regulated by hypoxia‐inducible factor (HIF‐1α), which strengthens the rationale of combining TACE with PD‐1/PD‐L1 inhibitors.…”
Section: Classes Of the Forerunner Checkpoint Molecules And Their Inhmentioning
confidence: 98%